Oxygen-Content Dependence of Cycle Performance and Morphology Changes in Amorphous-SiOx Thin-Film Negative Electrodes for Lithium-Ion Batteries. Issue 2 (25th January 2019) - Haruta, Masakazu; Doi, Takayuki; Inaba, Minoru
Abstract : The silicon–oxygen binary system (SiO x ) is a promising candidate as a negative electrode for next-generation lithium-ion batteries. Thin SiO x films of different oxygen contents were prepared by magnetron sputtering. Although almost all Si atoms in SiO x at low oxygen contents ( x = 0.21 and 0.48) contributed to the reversible alloying/dealloying reactions, an irreversible fraction of Si in SiO x at high oxygen contents ( x = 1.09 and 1.78) increased owing to the formation of Li4 SiO4 . In return for the decrease of reversible capacity, the capacity retention of heavily O-doped SiO x films improved owing to the buffer effect of Li4 SiO4 matrix against volume changes. The addition of vinylene carbonate (VC) to the electrolyte further improved the cyclability of the SiO x films, especially those of higher oxygen contents. For the pure-Si film, a sponge-like porous structure appeared after cycling owing to repeated crack formation and inhomogeneous volume changes, and resulted in massive electrode swelling. The morphology change with cycling was suppressed by the presence of Li4 SiO4 matrix and a homogeneous solid electrolyte interphase derived from VC, resulting in a superior cycle performance of the heavily O-doped SiO x negative electrodes.